Molecular identification of the virus causing yellow curl symptoms in local Katokkon Chili Plants (Capsicum chinense Jacq.) in West Sulawesi - Wiridannisaa, Nurul; Kasim, Niken Nur; Sukmawati, Sri; Ilham, Ilham (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2025)
Katokkon Chili is an important local variety in Mamasa, West Sulawesi, which frequently exhibits yellow mosaic and yellow curl symptoms. These symptoms are strongly suspected to be associated with viral infections, particularly those in the genera Begomovirus and Potyvirus. This study aimed to molecularly identify viruses causing yellow curl symptoms in Katokkon Chili plants. Symptomatic leaf samples were collected purposively from 14 locations in Mamasa Regency, West Sulawesi, followed by molecular detection and identification using universal Begomovirus and Potyvirus primers and sequencing analysis. Detection and identification results showed that chili plants yielded 912 bp DNA fragments with SPG1/SPG2 primers, confirming viral identity as Pepper Yellow Leaf Curl Indonesia Virus (PYLCIV) and demonstrating >98% homology with PYLCIV isolates from South Sulawesi. This study reports the first occurrence of PYLCIV in the Katokkon Chili variety in West Sulawesi and expands the host range of PYLCIV among chili varieties in Indonesia. These findings are important as a foundation for developing viral disease control strategies for chili plants in West Sulawesi.